DIAGNOSIS OF EDUCATIONAL AND COGNITIVE ACTIVITY OF STUDENTS BY TESTING METHOD - S.M. Shcherbyna; I.Yu. Shcherbyna (Academy of Cognitive and Natural Sciences, 2009)
In article the place of diagnostics in system of pedagogical monitoring is determined, the experience of use the testing as method of the control and estimating of results of cognitive activity of the students is submitted.